The demographic and serological characteristics of COVID-19 convalescent plasma donors: Identification of basic criteria for optimal donor selection. (April 2022) - Fazeli, Alieh; Sharifi, Shahin; Mohammadi, Saeed; Bahraini, Mehran; Arabkhazaeli, Ali; Jelveh, Nooshin; Eshghi, Peyman
Abstract: Background and Objectives: Convalescent plasma has attracted significant attention as a therapeutic option against infectious agents for more than a century. In March 2020, the use of Convalescent COVID-19 plasma (CCP) as a new research drug for COVID-19 treatment was approved by the FDA. The development of SARS-CoV-2 IgG antibodies following infection or vaccination is likely to be essential to provide adequate immunity for the population to halt the COVID19 pandemic. This study aimed to identify the criteria that would be used to determine the most appropriate CCP donors with the highest effective antiviral antibody titers. Materials and Methods: In this prospective cohort, univariate analyses and multivariate regression analyses were performed to evaluate the relationship between characteristics of 11949 CCP donors and COVID-19 disease severity prior to donation with antibody titers estimated using ELISA technique and rapid tests. Results: The antibody titer was measured among 8206 (68.7 %) donors. Elderly male and nulliparous female CCP donors who resided in the areas with high load of virus had positive ELISA and rapid test results as well as high levels of SARS-CoV-2 IgG antibodies titer. Moreover, the long hospital stay and elderly donors were the variables associated with high levels of SARS-CoV-2 IgG antibodies. Conclusion: This study suggests that nulliparous female and male donors with positive rapid tests who resided in areas with a higher prevalence of SARS-CoV-2, with more than 40 years of age and long hospitalization time can be the preferred donors for CCP donation.